Developing Carbon Particle Reinforced Aluminium Composite by Powder Metallurgy - Mohamad Najib Bin Mohtar, Mohamad Najib (2008)
The effect of sintering conditions (temperature, time, and atmosphere) was evaluated by cutting the disk and hardness was measured. SEM and EDX were used to study microstructural characterisation and particle content of the sintered materials. To improve the properties of pure aluminium disk, certain modification was made in the procedures.